A meta-analysis of long-term COVID-19 symptoms - Prantilla, Shi D.; Demayo, Cesar G.; Torres, Mark Anthony J.; Llantos, Orven E. (Intelektual Pustaka Media Utama, 2025)
This meta–analysis examines the far–reaching effects of long COVID (LC), highlighting the need for welfare strategies emphasizing the Parity of Esteem. The analysis of clinical studies reveals the prevalence of LC across various demographic factors, including age, gender, infection type, and severity. The findings highlight persistent pulmonary impairments that result in post-COVID pulmonary fibrosis (PCPF), long-term cardiovascular symptoms, gastrointestinal issues, dermatological concerns, and neuropsychiatric outcomes. These effects continue beyond the acute phase of COVID-19, affecting both symptomatic and asymptomatic people. The study emphasizes that LC is not only a physical ailment but also has a significant impact on mental health, necessitating a holistic approach to healthcare. Psychological and emotional distress among LC patients necessitates empathetic support. This study concludes by emphasizing the significance of LC and advocating for data-driven healthcare policies and assistance programs to address the unique challenges encountered by COVID-19 survivors. For managing the long-term effects of LC on both physical and mental health, an unwavering commitment to parity of esteem is crucial.